2020
DOI: 10.1186/s12991-020-00286-3
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior and metacognitive functions: a longitudinal study on patients with mental disorders

Abstract: Background: Metacognitive functions play a key role in understanding which psychological variables underlying the personality might lead a person with a severe mental disorder to commit violent acts against others. The aims of this study were to: (a) investigate the differences between patients with poor metacognitive functioning (PM group) and patients with good metacognitive functioning (GM group) in relation to a history of violence; (b) investigate the differences between the two groups in relation to aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Anger, evaluated using the STAXI-2, 35 also decreased significantly with increasing age, confirming that younger age is associated with a higher level of anger. As some authors have shown, 47 – 51 at least in people with psychotic disorders, anger might be the fundamental mediator between psychotic symptoms and the trigger of violent behaviour. Higher levels of anger, as detected with the STAXI-2, in young people and in people with personality disorders might be an extremely important therapeutic target: a reduction in anger might result in a reduction in the risk of aggressive and violent behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Anger, evaluated using the STAXI-2, 35 also decreased significantly with increasing age, confirming that younger age is associated with a higher level of anger. As some authors have shown, 47 – 51 at least in people with psychotic disorders, anger might be the fundamental mediator between psychotic symptoms and the trigger of violent behaviour. Higher levels of anger, as detected with the STAXI-2, in young people and in people with personality disorders might be an extremely important therapeutic target: a reduction in anger might result in a reduction in the risk of aggressive and violent behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Another Italian prospective study, comparing never aggressive with verbally, physically, and sexually aggressive male psychiatric patients, found that the latter had displayed an increased number of aggressive behaviors in the previous 2 years [71].…”
Section: History Of Aggressionsmentioning
confidence: 99%
“…For this reason, they may tend to express their thoughts and emotions through violent behavior toward others. 24 Based on these factors, we hypothesized that a history of physical violence reflects the high risk of physical violence in patients with BD-M.…”
Section: Discussionmentioning
confidence: 99%